Young children’s understanding of envy - Jensen de López, Kristine; Quintanilla Cobián, Laura; Giménez-Dasí, Marta; Sarriá Sánchez, Encarnación (Psyke & Logos, 2012)
Precursors of young children’s understanding of self-conscious emotions: envy across cultures